PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS NASABAH PADA BANK SYARIAH MANDIRI KCP PARIAMAN - Suherdi - (LPPM Universitas Muhammadiyah Sumatera Barat, 2017)
This study aims to determine whether the quality of care that includes physical evidence, reliability, responsiveness, assurance, and empathy effect on customer loyalty to the Bank Syariah Mandiri KCP Pariaman. The results of this study are expected to contribute to the banking company Bank Syariah Mandiri KCP Pariaman, and is expected to formulate a marketing strategy in order to maintain customer savings.The results of this study showed that simultaneous variable quality of service covering physical evidence, reliability, responsiveness, assurance, and empathy have a significant effect on customer loyalty gained significant value of 0.000 below 0.05. Based on the coefficient of determination can be seen that the independent variables explain the dependent variable of 25.1%, while the remaining 74.9% is explained by other variables in this case are not the subject of the study authors. Keywords: customer loyalty, service quality